The Use of Electronic Initiation Systems for Wall Control Blasting at an Open Pit Mine - Abil, Oraz; Bakhtybayev, Nurbol; Bakhtybayeva, Asel (Civil Engineering Journal, 2025)
This study investigates the effectiveness of electronic initiation systems (EIS) for wall control blasting in open-pit mining, with a specific focus on their influence on ground vibrations and rock fragmentation. The primary objective of the study is to evaluate whether EIS can achieve comparable or superior results in fragmentation quality while reducing seismic impact compared to non-electric initiation systems (NEIS). Experiments were conducted at an open-pit gold mine. During the experiments, EIS and NEIS were used. There was assessed seismicity of each blast during the experiments. Peak Particle Velocity (PPV) was measured at multiple points near the pit benches, and fragmentation of the blasted rock mass was analyzed through visual inspection and image analysis techniques. A statistical evaluation of the collected data revealed that EIS provided similar fragmentation outcomes while significantly reducing PPV values. Due to the ability to precisely time blasts and allow for optimized delay sequences and energy distribution, EIS can reduce blast vibrations. These findings suggest that EIS is a viable and efficient solution for wall control blasting, particularly in cases where pre-splitting or other conventional techniques cannot be applied due to geological or operational conditions. In this study, for the first time,the PPV was measured at the closest distance (6.57 m to the blasted block). The authors tried to find out the combination of two controversial outcomes of blasting work, rock fragmentation and ground vibrations, in this study.